Learning Application UI/UX Design Based on the Introduction of Indonesian Cultural Variety - Safitri, Dela; Kuncoro, Adam Prayogo; Hamdi, Aulia (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The problem of lack of understanding and appreciation for Indonesia's cultural diversity among children is increasingly emerging. This is due to the lack of effective and fun learning media, as well as the dominance of games that only contain entertainment without educational value. This research aims to develop a learning application that is specifically designed to introduce various Indonesia cultures to children. The method used to solve this problem is Design Thinking, which includes five stages: empathy, definition, ideation, prototyping, and testing. Through this stage, the design of the user interface (UI) and user experience (UX) that suits the needs of the user has been successfully created, with interesting and informative content regarding Indonesia's cultural diversity. The results of the application of this method were evaluated using the System Usability Scale (SUS), which tested the feasibility and effectiveness of the design. The app gets an average SUS score of 81, which indicates the B/Excellent category. Thus, this study successfully solved the problems identified and the methods used were successful so that it can be concluded that providing appropriate and interesting educational tools can increase cultural awareness among children.